2012
DOI: 10.2754/avb201281040371
|View full text |Cite
|
Sign up to set email alerts
|

Selected haematological and biochemical indicators in different breeds of rabbits

Abstract: The aim of the study was to evaluate differences in haematological and biochemical indicators in young rabbits of breeds embedded in the Czech genetic resources. Seven breeds (Moravian Blue, Czech Spotted, Czech Solver, Czech White, Czech Red, Moravian White of Brown Eyes and Czech Black Guard Hairs) represented by six males of each breed were used. Weaned rabbits were fattened under identical conditions till the age of 91 days. Haematological values were measured by using automatic analyzer; biochemical indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 16 publications
2
19
1
Order By: Relevance
“…Haematological parameters in mix-breed Polish rabbits with addition of blood of meat breed blood in annual cycle considering sex. Legend: ( ) -number of animals; x -mean value; SD -standard deviation, a -statistically significant difference between male and female, b -statistically significant difference between seasons (together), where b1 -statistically significant difference between spring and summer; b2 -statistically significant difference between spring and autumn; b3 -statistically significant difference between spring and winter; b4 -statistically significant difference between summer and autumn; b5 -statistically significant difference summer and winter; b6 -statistically significant difference between autumn and winter in the present study (Pintor and Grassini 1957, Fox and Laird 1970, Bortolotti et al 1989, Kabata et al 1991, Aleman et al 2000, Cazabon et al 2000, Rohilla et al 2000, Kim et al 2002, Burnett et al 2006, Chineke et al 2006, Olayemi and Nottidge 2007, Archetti et al 2008, Black et al 2009, Ç etin et al 2009, Jeklova et al 2009, Poljičak-Milas et al 2009, Abdel-Azeem et al 2010, Martinec et al 2012, Ö zkan et al 2012, Yaqub et al 2013). …”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Haematological parameters in mix-breed Polish rabbits with addition of blood of meat breed blood in annual cycle considering sex. Legend: ( ) -number of animals; x -mean value; SD -standard deviation, a -statistically significant difference between male and female, b -statistically significant difference between seasons (together), where b1 -statistically significant difference between spring and summer; b2 -statistically significant difference between spring and autumn; b3 -statistically significant difference between spring and winter; b4 -statistically significant difference between summer and autumn; b5 -statistically significant difference summer and winter; b6 -statistically significant difference between autumn and winter in the present study (Pintor and Grassini 1957, Fox and Laird 1970, Bortolotti et al 1989, Kabata et al 1991, Aleman et al 2000, Cazabon et al 2000, Rohilla et al 2000, Kim et al 2002, Burnett et al 2006, Chineke et al 2006, Olayemi and Nottidge 2007, Archetti et al 2008, Black et al 2009, Ç etin et al 2009, Jeklova et al 2009, Poljičak-Milas et al 2009, Abdel-Azeem et al 2010, Martinec et al 2012, Ö zkan et al 2012, Yaqub et al 2013). …”
Section: Discussionmentioning
confidence: 66%
“…On the other hand, the worldwide research have been performed on rabbits of different races (New Zealand, Agora, Czech and Sylvilagus Bachmani Riparius, cottontail, Soviet Chinchilla, grey giant, albino) and many unspecified mixed-breed rabbits, but only some of them have analysed the impact of the season of the year (Pintor and Grassini 1957, Black et al 2009, Ç etin et al 2009, Abdel-Azeem et al 2010, Yaqub et al 2013, sex (Fox and Laird 1970, Kabata et al 1991, Aleman et al 2000, Kim et al 2002, Burnett et al 2006, Chineke et al 2006, Black et al 2009, Ç etin et al 2009, Poljičak-Milas et al 2009, Abdel-Azeem et al 2010, Ö zkan et al 2012, Yaqub et al 2013, age (Bortolotti et al 1989, Chineke et al 2006, Olayemi and Nottidge 2007, Archetti et al 2008, Jeklova et al 2009, Yaqub et al 2013, and race of rabbits (Cazabon et al 2000, Rohilla et al 2000, Burnett et al 2006, Chineke et al 2006, Martinec et al 2012, Yaqub et al 2013. Also books (Feldman et al 2000, Harkness et al 2007 regarding reference values for haematological parameters in rabbits, present such values only for the New Zealand race, and do not account for environmental or physiological factors.…”
Section: Introductionmentioning
confidence: 99%
“…Haemoglobin concentrations in our study were significantly different among breeds. Breed effect was also confirmed by Abdel-Azeem et al (2010) within 4 pure breeds and their crossbreds and by Martinec et al (2012) within 7 medium-sized Czech national breeds. In our study, we found a positive significant correlation between the LW and the haematocrit value.…”
Section: Haematological Examinationmentioning
confidence: 64%
“…In our experiment, we found a considerably increased value for mean corpuscular volume in the Netherland Dwarf breed (99.0 fl). Also Martinec et al (2012) found significant differences in the value of mean corpuscular volume within seven medium-sized breeds (range of 73.8-83.0 fl). However, the values of mean corpuscular volume in our study displayed a wider range than that of Martinec et al (2012), which could indicate the specific effect of dwarf breeds on this haematological indicator.…”
Section: Haematological Examinationmentioning
confidence: 99%
“…: +48 91 444 1605 in peripheral blood have only been carried out in Poland on typical Polish mixed-breed rabbits (Table 1), while analogical foreign studies were performed on New Zealand and Fauve de Bourgogne rabbits, as well as LP and V genetic lines, and on Spanish mixed-breed rabbits (Table 2). Despite the fact that the studies were performed on a limited material, they are not determining reference values, and they were not assessed in the context of physiological and environmental conditions, which importance in rabbits was evidenced in the previous studies on haematologi- Legend: ns -not studied; x -mean value, SD ± -standard deviation cal factors (Pinna Pintor and Grassini 1957, Fox and Baird 1970, Laird et al 1970, Bortolotti et al 1989, Jain 1994, Rohilla et al 2000, Nowaczyk et al 2004, Nowaczyk et al 2005, Burnet et al 2006, Chineke et al 2006, Olayemi et al 2007, Archetti et al 2008, Black et al 2009, C etin et al 2009, Jeklova et al 2009, Poljičak-Milas et al 2009, Abdel-Azeem et al 2010, Martinec et al 2012, Ö zkan et al 2012, Yaqub et al 2013). The observations carried out in Poland on typical Polish mixed-breed rabbits showed the impact of animal age (Deptuła et al 1995) and season of the year (Nowaczyk et al 2004(Nowaczyk et al , 2005, while foreign studies performed on New Zealand, Angora, Czech rabbits and Sylvilagus Bachmani Riparius breeds, as well as mixed-breed rabbits, not only evidenced the impact of the age (Laird et al 1970, Bortolotti et al 1989, Chineke et al 2006, Olayemi and Nottidge 2007, Archetti et al 2008, Jeklova et al 2009…”
Section: Introductionmentioning
confidence: 92%